New South African Policy in Combating Xenophobia - ZANOSKINA Ekaterina Nikolaevna (Ученые записки Института Африки Российской академии наук)
The research is motivated by the extensive literature on the elevated levels of xenophobia in South Africa. The main contribution of the research to the academic field of ethnic conflict studies is that the author comprehensively approaches the determination of the level of xenophobia in South African society, whereas the majority of the literature on the issue has focused on the analysis of individual manifestations of xenophobic violence. This research was guided through three research questions: (1) what are the causes of xenophobia in South Africa? (2) What is the legal framework of South African policy addressing anti-migrant attacks? (3) What measures does the government of South Africa take to combat xenophobia? The principal purpose of the research is to help modernize South Africa’s policies, legislation and practices against xenophobia and related intolerance on the basis of the analysis proposed. Research methods included the study and analysis of literature and social surveys, the collection and analysis of factual materials, the study of documents, methods of quantitative and qualitative data processing.